Effect of Gluten Free diet (GFD) on blood sugar: a clinical trial - Shatakshi,; Kumar, B M N; Pandey, Ajai Kumar; Awasthi, H H (Journal of Postharvest Technology, 2021)
The present study was aimed to assess the effect of gluten free diet on the patients of type-II diabetes mellitus. Present findings shows that  how, short term intervention of GFD effects fasting and post prandial blood sugar of diabetes patients. Through randomization process 100  patients of already diagnosed type-II diabetes mellitus are registered for the study, within two groups (n=50).First group received a intervention  of gluten free diet(GFD) and other which was control group followed regular diet. The intervention was done for 12 weeks (3months), in which  biochemical parameters of FBS and PPBS was recorded initially and follow up was taken at an interval of each month. In comparison between  the two groups are seen through statistical analysis. Significant changes was seen in intervention group in fasting blood sugar (FBS) in  comparison to control group (p=0.000). However, less significant changes was observed in post prandial blood sugar (PPBS) (p=0.029). Gluten  free diet intervention for short interval helps in reduction of fasting blood sugar in type-II diabetes mellitus patients.GFD diet can act as a  preventive measure in type-II diabetes mellitus.
Keywords: Gluten free diet; type-II diabetes mellitus; fasting and post prandial blood sugar; diet intervention